Education and awareness of modern health care amongst aboriginal people: the case of the Jakuns of Peninsular Malaysia - Yew, Vivien C.W.; Sia, Mal-Kong; Lam, K.C.; Sarmila M.S.; Sivapalan Selvadurai (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2015)
Previous studies have indicated that the resettlement of the Orang Asli communities into areas nearer to towns was with the intention of improving the health conditions of the aboriginals. Subsequent researches have since focused on the relation between mainstream orthodox medical approaches and traditional healing practices in search of improved approaches to advance further the health cause of the aboriginal communities. However, none of these works have addressed the central question of how the Orang Asli have been adapting themselves to the mainstream healthcare system while still holding strong beliefs in their traditional medicine. To close the gap this study examined the readiness and intentions of the Orang Asli in adapting to modern health care approach amidst old traditional health beliefs and healings practices. A qualitative study based on in-depth interviews and field observations was carried out at a Jakun village of Kampung Kedaik, Rompin, Pahang involving 12 male and 13 female informants between 18 – 70 years old. Results of the study showed that as the Orang Asli people received proper education they appeared to think about health differently. Most of the informants preferred modern over traditional medicine predominantly because of their deteriorating faith in, and relative inaccessibility to traditional medicine. The findings implied that in this modern day most of the indigenous communities were open to social change which in this context included modern health care so as to improve their health conditions.